IMPLEMENTATION OF VILLAGE FINANCIAL SYSTEM (SISKEUDES) IN VILLAGE FINANCIAL MANAGEMENT IN PAMATANG ASILOM VILLAGE, GUNUNG MALELA DISTRICT, SIMALUNGUN REGENCY - Sri Wardani; Jhon Simon; Kariaman Sinag (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Abstract This study examines how the Village Financial System (Siskeudes) is implemented in village financial management at Nagori Pamatang Asilom, Gunung Malela Sub-district, Simalungun Regency, and identifies the supporting and inhibiting factors during its application. A qualitative descriptive method was used. Data were collected through in-depth interviews, field observation, and documentation. The informants consisted of the Pangulu, the Village Secretary who acts as the Siskeudes operator, the Head of Financial Affairs, the Chair of the Village Consultative Body (BPD), the Village Facilitator, and the Sub-district Section Head for Village Community Empowerment. Data were analysed using the interactive model of Miles and Huberman, while the implementation analysis adopted George C. Edwards III's framework. The findings show that Siskeudes has been applied across all stages of village financial management, namely planning, execution and administration, as well as reporting and accountability. Its application has improved transparency, accountability, and administrative orderliness. Several obstacles still occur. These include limited internet connectivity and VPN access, electricity outages, and the limited capacity of human resources in operating the application. The village government has responded through coordination with village facilitators, technical training, infrastructure improvement, and periodic data backup. The study concludes that the success of Siskeudes implementation rests on the integration of policy commitment, human-resource capacity, supporting infrastructure, and continuous mentoring and supervision. Keywords: Siskeudes; Village Financial Management; Policy Implementation; Transparency; Accountability